Infant attachment disorganization and moderation pathways to level and change in externalizing behavior during preschool ages. Issue 6 (1st November 2016) - Wang, Feihong; Willoughby, Michael; Mills-Koonce, Roger; Cox, Martha J.
ABSTRACT: This research examined the child, parent, and family conditions under which attachment disorganization was related to both level and change in externalizing behavior during preschool among a community sample. Using the ordinary least squares regression, we found that attachment disorganization at 12 months significantly predicted children's externalizing behavior at 36 months and this prediction was not contingent on any other factors tested. For predicting changes in externalizing behavior from 36 to 60 months, we found a significant main effect of family cumulative risk and an interaction effect between attachment disorganization at 12 months and maternal sensitivity at 24 months. Specifically, high disorganization was related to a significant decrease in externalizing behavior from 36 to 60 months when maternal sensitivity at 24 months was high. Our main-effect findings replicated the significant effect of attachment disorganization and cumulative risk on externalizing behavior with preschool-aged children. Our interaction finding provided support for understanding the parenting conditions under which infant attachment disorganization may be related to change in externalizing behavior during preschool ages. Implications of the findings were discussed.